Cover, Content, and Editorial Note from Pengabdianmu J Pengabdian Masyarakat Vol. 8 No. 1 January 2023 - Chief Editor of PengabdianMu J Pengabdian Masyarakat (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
Assalamu’alaikum Wr. Wb. Dear reader, now PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat re-published on Volume 8 Issue 1 January 2023. The publication of PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat certainly participate in disseminating the results of community services in science and technology development conducted by lecturers and researchers especially from UMPR and other universities. This edition contains 16 articles consisting of Education, Social and Political, Agriculture, and Health Science topics. Editorial boards are fully aware that there are still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank the University, all editors and reviewers, and contributors of the scientific articles who have provided the repetoire in this issue. We hope that all parties, especially the contributors of the articles, could re-participate for the success of the publication in the next edition on March 2023. Wassalamu’alaikum Wr. Wb.